SIMURG: Strategic intelligent framework for real-time 3D visualization and high-altitude analysis of global cyber threats - Das, Resul; Kaya, Muhammed Onur (European Alliance for Innovation, 2026)
The increasing volume and variety of cyber threats on a global scale make it difficult for security analysts to provide real-time situational awareness, pointing out the inadequacy of traditional two-dimensional (2D) visualization approaches. This study proposes SIMURG (Strategic Intelligent Monitoring and Unified Response Graph), a web-based and hardware-independent three-dimensional (3D) visualization system aimed at analyzing global cyber threats in real-time and intuitively. Named after the legendary bird of Turkic mythology to symbolize a sovereign, high-altitude perspective over the digital landscape, the system translates this metaphorical wisdom into a holistic monitoring framework. The system collects and processes cyber threat intelligence and OSINT-based data streams together with their timestamps, and visualizes source-target relationships, attack density, and geographic distributions on an interactive WebGL-based 3D globe. To support situational awareness, threat information is represented using multiple visual attributes, including color, height, and object size. Experimental evaluations indicate that SIMURG maintains an average rendering performance of 43.5 frames per second (FPS) while displaying 3,504 active nodes and up to 1,752 simultaneous attacks. When operating in batch analysis mode, supported by dedicated optimization algorithms, the refresh rate exceeds 144 FPS. In addition, analyses conducted on six months of historical data show that the system can reveal recurring temporal patterns in cyber threats and provide useful insights for operational decision-making. Copyright © 2026 Resul Das et al., licensed to EAI. This is an open access article distributed under the terms of the CC BY-NC-SA 4.0, which permits copying, redistributing, remixing, transforming, and building upon the material in any medium so long as the original work is properly cited.
Keywords: Cyber Attack; Cyber Threat Intelligence; Cyber Threat Visualization; Real-Time Visualization; Situational Awareness; Webgl Visualization